ปัจจัยในการคัดเลือกผู้ประกอบการขนส่งสินค้าอุปโภคบริโภคด้วยรถบรรทุก - ปิยะกรณ์ สุนทรวัฒน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This research has the objective for analyses the latency of the transportation service with respond the requirement of consumer goods or consumer good shippers, in the middle area of the consumer goods carriers company. We focus to study the group of customer in Bangkok area, the perimeter and provincial area, together with make the suggestion for latency development competition in this business in order to have a guideline for improvement and development of transportation service with respond the requirement of customer. We divide the survey in 2 times together. The 1st times of survey, we have the objective for evaluate latency service of the transportation company, the type of the questionnaire is use the direct question in latency level, importance level or transportation company expectation and then we analyse by use the gap analysis and quadrant analysis. The 2nd times of survey, we have the objective for seeks the weight of importance factor that obtain from the 1st times survey for brings it’s to make the suggestion for latency development competition by use the analytical hierarchy process technique. The result of this research found the importance factor in modern trade group in Bangkok and the perimeter area are give precedence to service level come first and freight rate in the second. In traditional trade group in Bangkok and the perimeter area are give precedence to freight rate come first and service level in the second. And in the traditional trade in provincial area are give precedence to freight rate come first and period of time from starting point to the destination in the second.